Steam Reforming Of Glycerol Over Alkali promoted Co-Ni/Al2o3 Catalysts - Cheng, C. K. (2010)

(untitled)
The steam reforming of glycerol over 5Co-10Ni/Al2O3 catalysts promoted with Group I metals (2.5wt%) has been investigated. All catalysts were prepared by wetness coimpregnation of the metal nitrates and calcined at 873 K. Reforming reaction was carried out in a fixed-bed micro-reactor at 723 to 823 K under atmospheric pressure. BET surface are of the fresh catalysts decreased from 180 (for the unpromoted catalyst) to 125 m2 g-1 (for the Li-doped catalyst) although within the promoted catalysts, the area increased down the group attaining a maximum in the K-catalyst. Pore volume, however, remained insensitive to alkali addition. TPR profiles revealed that the alkali promotion decreased the reduction temperature for the various oxide phases in the Co- Ni/ Al2O3 catalyst.Reforming runs revealed that H2:CO2 ratio (2.30 to 2.40) on all catalysts were in agreement with stoichiometirc expectation (2.33) at 823 K but gradually increased with decreasing temperature. The K-promoted catalyst gave the best activity. All promoters, with the exception of Cs, reduced the activation energy for H2 and CO2 production. Indeed, a compensation effect was observed within the Group I metals with different isokinetic temperatures for the pairs, H2 and CO2 as well as for CO and CH4. This suggests that the two pairs of products were most likely formed via different reaction pathways. In particular, while H2 and CO2 were primary products from the reforming reaction, CO and CH4 arose from secondary hydrogenolysis of glycerol. Post-reaction characterisation of the used catalysts indicated that the superior activity of the K-promoted catalyst was probably due to stronger glycerol adsorption and hence, higher carbon deposition. The latter was, however, completely removable via TPR-TPO cycle which itself implicated the existence of at least two types of carbon deposits – a carbonaceous pool inert to H2 and another reactive with both O2 and H2.